Le bénévolat, un soutien au maraîchage professionnel agroécologique en phase d’installation - Julie Hermesse; Maëlle Van der Linden; Lou Plateau (VertigO, 2020)
This article questions the contribution of voluntary labour in agroecological gardening on small surfaces. When voluntarily resorting to limited motorization as well as ecological principles of production, labour proves to be a precious resource. Whether it be professional, family, amical or officialized, within the context of a training agreement or voluntary work, every labour source is welcome during the launch phase of a market-gardening project. These two observations lead us to pose the following hypothesis: having a voluntary work force is a factor, which can contribute to the successful installation of an agroecological market gardening project. The reflections proposed result from participative observations and analyses carried out in a participative way with market-gardening project stakeholders about their working hours and those contributed by volunteers in their fields. These experimental gardening arrangements, combining professional and voluntary market gardening, invite us to reflect on the conditions needed – in the area of social and organizational resources - for launching a project and making their professional activities economically and socially durable. Lastly, and more broadly, this article wishes to contribute to reflection on the connection between the mobilization of volunteers and the viability of economic alternatives.